Diagnose da deficiência nutricional e crescimento do Bastão-do-Imperador Etlingera elatior (Jack) R. M. Smith com o uso da técnica do elemento faltante em solução nutritiva - Frazão, Jussara Ellen Morais (2008)
This work was carried out with the objective of characterizing typical and individual symptoms of both B and macronutrients nutritional deficiency, as well as evaluating their effect on the mineral composition of torch ginger plants through micro and macronutrient analyses. The experiment was conducted from January 2007 till January 2008 under greenhouse conditions at the Soil Science Department of Federal University of Lavras (Lavras, MG, Brazil), using a randomized block design with four replications and eight treatments. The treatments consisted in: i) a complete Hoagland & Arnon Solution (1950); ii) a nutrient solution without N (-N); iii) a nutrient solution without P (-P); iv) a nutrient solution without K (-K); v) a nutrient solution without Ca (-Ca); vi) a nutrient solution without Mg (-Mg); vii) a nutrient solution without S (-S); and, viii) a nutrient solution without B (-B). Visible and characteristic symptoms were observed in all plants under nutrient deficiency. Deficiency symptoms first occurred in treatments where B, N, S, and K were absent, followed by treatments without P, Mg, and Ca. The torch ginger plants demanded more B, K, N, P, and S than Ca and Mg at the beginning of the growth period. Reduction in plant dry matter production occurred mostly associated with the following order of nutrient deficiency: B >K> N> P> S> Mg> Ca. Macronutrient contents in torch ginger leaves of plants growing in the complete Hoagland & Arnon solution were as follows (g kg-1): N 26.92; P 2.44; K 22.80; Ca 13.70; Mg 3.30; S 1.98. Micronutrient contents found in torch ginger leaves for the aforementioned solution were as follows (mg kg-1): B 38.25; Cu 4.58; Fe 174.62; Mn 138.87; Zn 34.64. Both macronutrient and B deficiencies were found to change the content and the accumulation of macro and micronutrients in different plant parts.